LaSr3NiRuO4H4: a 4d transition-metal oxide-hydride containing metal hydride sheets - Jin, L; Lane, M; Zeng, D; Kirschner, F; Lang, F; Manuel, P; Blundell, S; McGrady, J; Hayward, M (Wiley, 2018)
We report the synthesis of the first 4d transition metal oxide-hydride, LaSr3NiRuO4H4, prepared via topochemical anion exchange. Neutron diffraction data show that the hydride ions occupy the equatorial anion sites in the host lattice and as a result the Ru and Ni cations are located in a plane containing only hydride ligands - a unique structural feature with obvious parallels to the CuO2 sheets present in the superconducting cuprates. DFT calculations confirm the presence of S = ½ Ni1+ and S = 0, Ru2+ centres, but neutron diffraction and μSR data show no evidence for long-range magnetic order between the Ni centres down to 1.8 K. The observed weak inter-cation magnetic coupling can be attributed to poor overlap between Ni 3d_(z^2 ) and H 1s in the super-exchange pathways.